Correlation between in vitro tests for blood brain barrier penetration with in vivo gliclazide penetration - Lalic-Popovic, M.; Vasovic, V.; Al-Salami, Hani; Golocorbin-Kon, S.; Milijasevic, B.; Mikov, M. (Excerpta Medica, Inc., 2013)
Aim: The aim of this study was to investigate whether in vitro models of gliclazide distribution in systems n-octanol/water and cyclohexane/water are good in vitro models for the prediction of its penetration as well as for the prediction of influence of dexycholic acid (DCA) influence on penetration. Patients (or Materials) and Methods: Distribution coefficient (logD) was determined using a …Flask shake “method. Partition profile was determined over physiological pH range (from pH 1.2 HCl solution, pH 4.5 acetate buffer, pH 6.8 and 7.4 phosphate buffer, and pH 7 distilled water) for 5 combinations of n-octanol or cyclohexane with aquase gliclazide solution (10 µg/mL) of different pH and with or without the addition of DCA (0.5 mM) into n-octanol or cyclohexane phase. The analyses were done in triplicate for each pair of organic solvent/ water. Concentrations of gliclazide were determined using high-performance liquid chromatography. Values of logD at pH 7.4 were compared with literature date of gliclazide BBB penetration and influence of DCA on it penetration.Results: Higher partition into organic layer was found in system n-octanol/water than cyclohexane/water. Also DCA increased partition of gliclazide in system cyclohexane/water but not in system n-octanol/water. Value of logD at pH 7.4 without DCA in organic layer in system n-octanol/water was 0.34 (0.05) and in system cyclohexane/water was –0.74 (0.11). Value of logD at pH 7.4 with DCA in organic layer in system n-octanol/water was 0.54 (0.07) and in system cyclohexane/water was 0.18 (0.01). Thus, partition of gliclazide in system cyclohexane/water better correlate with in vivo data where penetration of gliclazide was increased with DCA pretreatement, but in diabetic animals, penetration was increased in group with and without DCA pretreatment what this in vitro system could not predict. Conclusion: Investigated system cyclohexane/water predicted poor gliclazide BBB penetration and the influence of DA on gliclazide penetration but system n-octanol/water failed to do so. However, more substances are need to claim that system cyclohexane/water successfully could predict drugs BBB penetration.